Project on Human Development in Chicago Neighborhoods (PHDCN): Alcohol Use Follow-Up, Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Alcohol Use Follow-Up survey. It was adapted from the Diagnostic Interview Schedule (DIS-IV) Alcohol Module and was administered to subjects in Cohorts 15 and 18. It collected information regarding the use of alcohol by the subjects as well as social or health problems resulting from drinking.